TEKNIK PEMBENIHAN UDANG VANNAMEI (Litopenaeus vannamei) DI HATCHERY PT. DELTA WINDU PURNAMA KABUPATEN SITUBONDO PROVINSI JAWA TIMUR - Halim, Atika Marisa; Suprakto, Bambang; Adriant, Nathania Nabilah (Jurnal Perikanan Pantura (JPP), 2025)
Larvae quality is the main input for the success of vannamei shrimp cultivation. Quality of larvae are produced with optimal production handling through standardized hatchery units. PT Delta Windu Purnama is one of the companies engaged in shrimp hatchery. This study aims to determine the results of shrimp larvae production such as Fecundity, Fertilization Rate, Hatching Rate, Survival Rate and Population at the Hatchery of PT. Delta Windu Purnama Situbondo, East Java. This study was conducted during one cycle in shrimp hatchery from November to December 2024. This study was conducted on modules A and B with concrete construction. The vannamei shrimp broodstock is F1 broodstock from Bencmark Genetic Shrimp. The nauplii that are spread are nauplii types N4 and N5. The feed given is in the form of natural feed such as Chaetocheros sp., Artemia salina and blended artificial feed and spread artificial feed. The fecundity obtained is 320.000 eggs/broodstock. Module A obtained Fertization rate of 90% and for module B it is 95%, then for SR in module A it is 79% and module B it is 87%. Egg hatching rate obtained is 85.7%. Based on the results of the research that has been done, module B shows better results compared to module A.